Observations of a Quickly Flapping Interplanetary Magnetic Reconnection Exhaust - Wang, Jiemin; Zhao, Yan (Frontiers in Physics, 2021)
On the basis of the Petschek reconnection model and the characteristics of reconnection, hundreds of reconnection exhausts were reported in the solar wind. Many multi-spacecraft observations also indicated that interplanetary magnetic reconnection is a quasi-steady-state plasma process and the reconnection X-line can extend hundreds of Earth radii. In this study, we report an interplanetary flapping reconnection exhaust observed by Wind on April 1, 2003 at 1 AU. The magnetic reconnection event has two adjacent accelerated flows. We compared the plasma and magnetic characteristics of the two accelerated flows, and found that the second accelerated flow was due to the back-and-forth movement of the reconnection exhaust. Our observations reveal that not all interplanetary reconnections operate in a quasi-steady-state manner, some reconnection current sheets can move rapidly back and forth.